Research on Responses of Digestive and Metabolic Enzymes to Different Feeding Strategies with Sub-optimal Protein Level in Labeo rohita Fingerlings - Pankaj Kumar; K. K. Jain; S. Munilkumar (Current Advances in Chemistry and Biochemistry Vol. 2, 2021)
A 60-days feeding trial was conducted to study the effect of different feeding strategies with normal and low protein diet on digestive and metabolic activity in Labeo rohita fingerlings. Labeo rohita is the most important Indian Major Carp (IMC), which is cultivated commercially across the country. One hundred thirty five fingerlings were distributed in triplicate groups of each treatment. Three experimental isocaloric (401.32 to 410.28 kcal/100 g) diets of 30%, 25% and 20% crude protein designated as diet A, diet B and diet C respectively were prepared, using locally available feed ingredients. Three different feeding schedules of normal protein diet continuously (diet A-30%) throughout the experiment, alternate feeding of 1-day diet A followed by 1-day diet B (1A/1B) and alternate feeding of 1-day diet A followed by 1-day diet C (1A/1C) through- out the experiment were tested by feeding the fishes at 5% body weight daily. Results showed that digestive enzymes activity such as protease and amylase was higher in the group fed 1A/1B. Glucose 6 phosphatase (G6Pase) were also analysed. The metabolic enzymes such as lactate dehydrogenase (LDH), malate dehydrogenase (MDH) are reported to be significantly difference (p<0.05) in among the different feeding schedules. The proteolytic activity such as alanine amino transaminase (ALT), aspartate amino transaminase (AST), alkaline phosphatise (ALP) were reported to be higher in the group fed with 1A/1B feeding schedule.